Development of an AI-Based Chatbot to Support Non-Formal Islamic Education: Integrating AI as an Interactive and Innovative Medium - Tammam Sholahudin; Hafidz Hafidz (Universitas Muhammadiyah Surakarta, 2025)
The rapid advancement of information and communication technology has transformed educational practices, particularly with the integration of artificial intelligence (AI). One emerging innovation is the chatbot, which provides interactive and personalized learning experiences. This study aims to develop an AI-based chatbot, named Chat63, to support the educational framework of Tapak Suci Putera Muhammadiyah, an autonomous organization under Muhammadiyah that integrates martial arts training with Islamic values. Positioned within the scope of non-formal Islamic education, Tapak Suci functions not only as martial arts training but also as a medium of character building, spiritual strengthening, and the implementation of Al-Islam and Muhammadiyah values. Utilizing the Research and Development (R&D) approach with the ADDIE model, Chat63 was designed to deliver Tapak Suci’s cognitive materials, including organizational knowledge, Tapak Suci principles, Al-Islam, Muhammadiyah studies, and Tapak Suci traditions. Evaluation results indicate that Chat63 effectively provided accurate, relevant, and fast responses, enhancing learners’ engagement and understanding. While improvements such as visual aids and concise responses are still needed, Chat63 demonstrates strong potential as an innovative and interactive learning medium that bridges non-formal Islamic education, tradition, and modern technology.